APLIKASI GAME PENGENALAN WISATA KOTA SEMARANG DENGAN METODE COLLISION DETECTION - FADHLULLOH, KHOLED; TH.D, Wismarini (Information Technology and Telematics, 2018)
Abstract The city of Semarang can be classified as a metropolitan city in Central Java Province. With a status as a metropolitan city filled with interesting attractions, the city of Semarang is one of the tourist destinations of local and foreign tourists. Semarang has many tourist attractions to be proud of, one of which is a historic building. Historic buildings are heritage buildings from our ancestors. Historic buildings generally have unique characteristics so they can be admired and preserved. Along with the times, therefore, this study aims to find out how to make applications for Android-based "Building Tours" Games that are expected to be used in the process of introducing historic buildings to children so that they can always maintain inheritance from existing ancestors. The method used in this research is coillision detection, used to detect collisions between objects in the game, this game has a map based on the city area of ​​Semarang that is made like a forest, in the game there are 4 historic buildings including young monuments, supporting , mixed church, and sewu lawang. Tests are carried out using 2 android devices with different specifications. The results showed that the game "building tour" made using construct 2 can be run on a mobile device with an Android platform easily by users.